Liver cancer oncogenomics: opportunities and dilemmas for clinical applications. (January 2015) - Marquardt, Jens U; Andersen, Jesper B
SUMMARY : Primary liver cancers are among the most rapidly evolving malignant tumors worldwide. An underlying chronic inflammatory liver disease, which precedes liver cancer development for several decades and frequently creates a pro-oncogenic microenvironment, impairs progress in therapeutic approaches. Molecular heterogeneity of liver cancer is potentiated by a crosstalk between epithelial tumor and stromal cells that complicate translational efforts to unravel molecular mechanisms of hepatocarcinogenesis with a drugable intend. Next-generation sequencing has greatly advanced our understanding of cancer development. With regards to liver cancer, the unprecedented coverage of next-generation sequencing has created a detailed map of genetic alterations and identified key somatic changes such as CTNNB1 and TP53 as well as several previously unrecognized recurrent disease-causing alterations that could contribute to new therapeutic approaches. Importantly, these investigations indicate that a classical oncogene addiction cannot be assumed for primary liver cancer. Therefore, hepatocarcinogenesis can be considered a paradigm suitable for individualized medicine.